2011
DOI: 10.1021/nn102291j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Chemical Enhancement of SERS by Controlling the Chemical Reduction of Graphene Oxide Nanosheets

Abstract: Chemical enhancement is an important mechanism in surface-enhanced Raman spectroscopy. It is found that mildly reduced graphene oxide (MR-GO) nanosheets can significantly increase the chemical enhancement of the main peaks by up to 1 order of magnitude for adsorbed Rhodamine B (RhB) molecules, in comparison with the mechanically exfoliated graphene. The observed enhancement factors can be as large as ∼10(3) and show clear dependence on the reduction time of graphene oxide, indicating that the chemical enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
279
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(293 citation statements)
references
References 41 publications
14
279
0
Order By: Relevance
“…This enhancement was attributed to the charge transfer between graphene and the molecules, which result in a chemical enhancement. More recently, Yu X. et al (Yu, Cai et al 2011) showed that mildly reduced GO (MR-GO) nanosheets can significantly increase the chemical enhancement of the main peaks by up to www.intechopen.com 1 order of magnitude for adsorbed Rhodamine B (tested molecule), in comparison to mechanical exfoliated graphene. The observed enhancement factors can be as large as 10 3 and show clear dependence on the reduction time of GO, indicating that the chemical enhancement can be steadily controlled by specific chemical groups.…”
Section: Nobel Metal/graphene Nanocomposites As Sers Substratesmentioning
confidence: 99%
“…This enhancement was attributed to the charge transfer between graphene and the molecules, which result in a chemical enhancement. More recently, Yu X. et al (Yu, Cai et al 2011) showed that mildly reduced GO (MR-GO) nanosheets can significantly increase the chemical enhancement of the main peaks by up to www.intechopen.com 1 order of magnitude for adsorbed Rhodamine B (tested molecule), in comparison to mechanical exfoliated graphene. The observed enhancement factors can be as large as 10 3 and show clear dependence on the reduction time of GO, indicating that the chemical enhancement can be steadily controlled by specific chemical groups.…”
Section: Nobel Metal/graphene Nanocomposites As Sers Substratesmentioning
confidence: 99%
“…However, as it was experimentally observed originally in 2010 by Ling et al [1], the Raman intensity of phthalocyanine, rhodamine 6G, protoporphyrin IX, and crystal violet molecules all have very different enhancement factors. Furthermore, it has been shown that enhancement factors are strongly dependent on which molecule is being probed, on the laser excitation energy used, on the two-dimensional (2D) material used for the enhancement surface [8][9][10] and even on the Fermi energy of the system, as controlled by a gate voltage [6,11,12]. The dependence of the enhancement on all these parameters cannot be explained either in terms of multiple reflections, nor by the quenching of the luminescence, nor even by a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…13−15 Recent findings also sustained the convenient use of GO and of mild reduced GO in generating SERS signals that accurately resemble the native spectrum of the molecules in solution without frequency shifts, which instead are typically generated as a consequence of the interaction with graphene or metal. 16 Overall, veiling plasmonic nanoparticles with GO sheets is perceived as a favorite strategy to fabricate advanced SERS substrates which hold the promise of improved sensitivity, signal stability, and reproducibility.While complex and laborious procedures are needed for coupling graphene to nanostructured surfaces, 7,8,17 GO coating can be simply obtained by physisorption of GO sheets in …”
mentioning
confidence: 99%